Chirality from Molecular Electronic States - Akitsu, Takashiro (IntechOpen, 2019)
In chemistry, biology, and physics, "chirality" is an important concept in nature. Especially in chemistry, not only classical stereochemistry but also asymmetric organic synthesis, supramolecular chemistry, construction of bio-related molecules and molecular recognition became indispensable structural chemical keywords. However, in view of synthetic chemistry and its structural chemistry, chemistry dealing with chirality in relation to the more fundamental electronic state is still a minority. This book is particularly aimed at chiroptical spectroscopy, structural or physical features and theoretical computation of chirality.